Pseudoartrosi settiche e asettiche dell’arto inferiore - Salomone, C.; Burastero, G.; Antonini, A.; Carrega, G.; Biasibetti, A.; Riccio, G. (Lo Scalpello - Journal, 2019)
ASEPTIC AND SEPTIC NONUNIONS IN LOWER LIMB Nonunion is a dangerous orthopaedic complication. The purpose of this work was to provide an indication for the diagnosis, classification and treatment of nonunions. The technique for treating aseptic nonunions depends on viability of the site. Therapeutic intervention create a mechanical and biological situation positive to achieve the treatment. In septic cases, the method consists in oncological debridement of bone and soft tissue and reconstructive surgery. Circular fixation plays an active role.